BANK SYARIAH DALAM PERSPEKTIF NASABAH MUSLIM - Multazam Mansyur Addury (SEKOLAH TINGGI AGAMA ISLAM AL-HUSAIN MAGELANG, 2017)
Islamic banks that emerge with the concept of interest-free banking are less well received by the public. The development of Islamic banking in Indonesia, accompanied by the emergence of groups who lack confidence in the ability and credibility of Islamic banking. Negative views on Islamic banks can lead to the emergence of social prejudice against Islamic banks. This study uses the postpositivist paradigm with exploratory research design. The sample to be used in this study amounted to 10 of the Muslim customers of conventional banks in the city of Yogyakarta. The data collection techniques used are interviews. The analysis technique uses qualitative descriptive analysis. The results of the study concluded that in terms of stereotypes the respondents did not know clearly related to Islamic banking, respondents considered Islamic banks currently running not in accordance with the existing concepts, some even argued that the application of Islamic banks was the same as conventional banks. Based on the aspects of beliefs and judgments, respondents were only able to mention the impact of the existence of Islamic banks in terms of religiosity only but could not mention real impacts in the community. Based on emotional aspects, respondents felt positive emotions related to Islamic banks and considered Islamic banks to be better than conventional banks but respondents tended to prefer to use conventional banking services. Based on the favorability and liking aspects, respondents considered Islamic banks to be better than conventional banks and respondents felt interested in knowing more about Islamic banks and joined as sharia bank customers